Development Of Strategic Organizational Learning As A Competitive Advantage In The "Paladars" Of The Sector Sme’s Horeca In The Havana, Cuba - Nuricumbo-Castro, Héctor; Moguel-Liévano, Manuel; González-Pérez, Manuel (European Scientific Journal, ESJ, 2016)
The research develops a model of Strategic Organizational Learning (SOL) to acquire and build institutional knowledge as a long-term competitive advantage in family businesses known as paladars. It aims to consolidate and strengthen the SME Horeca sector in Havana, Cuba. The proposed methodology is not experimental and correlational cross-sectional. The Knowledge Transfer equation was implemented to measure the SOL based on the proposed model. Also, it was used to determine the relationship between learning and competition. The equation was validated. The results indicated that most paladars present an SOL Medium/Regular, and independence exists between competition and learning. However, there is great ignorance to foster the organizational culture in the HORECA sector. This study suggests that the arrival of US competition causes these establishments perish.